WEBSITE DESIGN OF DANAU SEMBULUH SUBDISTRICT SERUYAN DISTRICT CENTRAL KALIMANTAN E - GOVERNMENT BASED GOVERNMENT TO CITIZEN MODEL - Abertun Sagit Sahay; Nugraha Sagit Sahay (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
District Office is a government service district level. Until now, this government is less thanoptimal in the dissemination of information because they still use manual methods such announcementand leaflets in his ministry. Rapid pace of technological developments and the government issued an egovernmentsystem that can easily provide information and services to the public that is easily accessibleby the public. The design of this website is a stage in the development of software in this website districtsthat will be used in the final stage in order to obtain a product website.In the design of this subdistrict website using waterfall methodology that has five (5) stages.Stages include Analysis, Design, Coding, Testing, Maintance. In designing this website using themethodology of the stage just to pad analysts and design stage, this stage is used in the Unified ModelingLanguage (UML), which consists of usecase diagrams, activity diagrams and class diagrams.Level of e-government website Sembuluh District of Lake is located on level 1, which is thelevel where there is an application Preparation surrounding G2C services. Website G2C services whichinclude the dissemination of information to the public with the availability of news pages, download,profile, agenda, gallery, maps and online regristerasi used in the registration of National Identity Card,Family Card and Certificate of Business. From the results of this analysis shows that the actors involvedin is admin which is the highest user who will manage the overall website. And other actors are visitors auser. Class diagram is formed consisting of the management module, download, agenda, businesscertificate, domicile certificate, identity card, KK, albums, gallery, news, category, submenus,menuutama, comments, katajelek, Contact us, map, haltambahan, dataadmin, templates .